Paraguay: Two opposed models of Public Policies in Poverty - Daniel Campos; María Celsa Benavidez (Población y Desarrollo, 2019)
This article compares two contrasting models of Public Policies in the Fight against Poverty within the framework of the TENONDERÁ Program of the Secretariat of Social Action - SAS and within the framework of the “Sembrando Oportunidades”, Program of the Technical Planning Secretariat - STP. It wants to contribute to illuminate the debate of what would be the model of intervention adapted to the Paraguayan reality to develop social changes in the process of institutional intervention of more efficient and effective public policies against poverty. The study presented finds better results within the framework of a model that incorporates the social dimension and the concept of poverty as exclusion. The study presented finds better results within the framework of a model that incorporates the social dimension and the concept of poverty as exclusion.